2016
DOI: 10.1186/s12943-016-0558-7
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 in the regulation of cell metabolism: a cancer perspective

Abstract: Caveolin-1 (CAV1) is an oncogenic membrane protein associated with endocytosis, extracellular matrix organisation, cholesterol distribution, cell migration and signaling. Recent studies reveal that CAV1 is involved in metabolic alterations – a critical strategy adopted by cancer cells to their survival advantage. Consequently, research findings suggest that CAV1, which is altered in several cancer types, influences tumour development or progression by controlling metabolism. Understanding the molecular interpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
137
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(141 citation statements)
references
References 116 publications
2
137
0
2
Order By: Relevance
“…In line with this study, overexpression of caveolin 1 is shown to increase cholesterol efflux and reduce the proliferation of human skin fibroblasts [51]. However, dysregulation of caveolin 1 expression is found in multiple types of cancer [52,53,54]. It should be clarified in which cellular context caveolin 1 functions as a tumor suppressor or an oncogene and whether altered intracellular cholesterol levels by caveolin 1 could suppress or promote cancer progression.…”
Section: Regulation Of Lipid Metabolism By Wild-type P53mentioning
confidence: 56%
“…In line with this study, overexpression of caveolin 1 is shown to increase cholesterol efflux and reduce the proliferation of human skin fibroblasts [51]. However, dysregulation of caveolin 1 expression is found in multiple types of cancer [52,53,54]. It should be clarified in which cellular context caveolin 1 functions as a tumor suppressor or an oncogene and whether altered intracellular cholesterol levels by caveolin 1 could suppress or promote cancer progression.…”
Section: Regulation Of Lipid Metabolism By Wild-type P53mentioning
confidence: 56%
“…In fact, in ours results we demonstrated that GRX EGFP‐Cav1 cells endocytosed more FluorSpheres® when compared with GRX. Importantly, Cav‐1 and its interactions with actin cytoskeleton and ATP play a pivotal role in the structure, formation, and function of caveolae . Although these results may be related to the increase on the caveolae number, it is possible that FluorSpheres® uptake can be being driven by both caveolar endocytosis or clathrin‐dependent endocytosis …”
Section: Discussionmentioning
confidence: 99%
“…TP53‐induced glycolysis and apoptosis regulator was further upregulated in the co‐cultured breast cancer cells, which resulted in apoptosis inhibition, and thus supports the hypothesis that stromal CAV1 possesses tumor‐suppressor properties, whereas loss of stromal CAV1 fosters malignant epithelial cell resistance by evading apoptosis . Thus, restoring CAV1 expression in respective stromal cells could inhibit the cancer cell metabolism . Excessive reactive species not only induce oxidative damages and inactivation of tumor suppressor genes but also activate the phosphorylation of CAV1, which was reported to promote cancer cell growth and survival .…”
Section: Introductionmentioning
confidence: 99%
“…Another resistance promoting factor is autophagy, as cancers can upregulate autophagy to survive microenvironmental stress and to increase growth and aggressiveness . CAV1 was already directly associated with autophagy . In CAV1 expressing human breast cancer cells the expression of CAV1 and autophagy‐related proteins were induced and inhibited apoptosis upon Estradiol treatment, a crucial regulator of cell growth by mediating autophagy and apoptosis in breast cancer cells .…”
Section: Introductionmentioning
confidence: 99%